Limbah Bata Ringan untuk Bahan Campuran Agregat Halus Terhadap Kuat Tekan Pada Beton K-250 - Sigit Agung Priyono; Hammam Rofiqi Agustapraja (Jurnal Teknik, 2021)
Light brick waste is fragments or pieces of scrap leftover during the installation of lightweight bricks which are often allowed to pile up and becoming garbage in the surrounding area. The waste is difficult to recycle and has a very low selling value. This study aims to assess the compressive strength of mixed composition concrete specimens using lightweight brick waste on the quality of K-250 concrete aged 7 days as a mixture of fine aggregate concrete so that it becomes a product that has better-added value for the community. The research method used in this research is SNI for concrete based on data from literature and the test was carried out in the UNISLA laboratory. The results showed that the use of a 0% mixture of lightweight brick waste resulted in compressive strength of 21.78 Mpa, 3% mixture yielded compressive strength of 18.87 Mpa, 5% mixture yielded compressive strength of 24.39 Mpa, and 7% mixture yielded compressive strength of 26.00 Mpa.